A lead-free ligand-free halide perovskite nanomaterial and its preparation method and application

The hollow spherical structure of halide perovskite nanomaterial Cs3Sb2Br9 was prepared by a ligand-free method, which solved the problem of low performance of lead-free perovskite photocatalysts and achieved efficient photocatalytic CO2 reduction and methanol oxidation reaction.

CN116375082BActive Publication Date: 2025-04-04TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310331965.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-04-04
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

The existing lead-free perovskite photocatalysts have low photoelectric properties, and due to the existence of long-chain organic ligands at the end cap, electron transfer is poor and active sites are exposed, resulting in poor catalytic effect.

Method used

The halide perovskite nanomaterial Cs3Sb2Br9 with hollow spherical structure was prepared by a ligand-free method. By dissolving SbBr3 and CsBr in DMSO, quickly adding methyl acetate to form a shell, and gradually forming a hollow spherical structure.

Benefits of technology

The preparation of lead-free and ligand-free halide perovskite hollow nanospheres was achieved, which solved the problem of great toxicity of lead-based perovskites, and improved the light absorption capacity and catalytic activity of the photocatalyst, especially in CO2 reduction and methanol oxidation reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004155235810000011
    Figure HDA0004155235810000011
  • Figure HDA0004155235810000012
    Figure HDA0004155235810000012
  • Figure HDA0004155235810000021
    Figure HDA0004155235810000021
Patent Text Reader

Abstract

The present invention discloses a lead-free, ligand-free halide perovskite nanomaterial, a preparation method and an application thereof. The halide perovskite Cs3Sb2Br9 nanomaterial of the present invention is hollow spherical and is constructed by a simple template-free method without the need for a surfactant. Compared with the halide perovskite of the traditional solid nanostructure, the hollow nanostructure enables the prepared halide perovskite catalyst to have a better photocatalytic effect. More importantly, while reducing carbon dioxide, methanol can be oxidized to produce value-added formic acid close to the stoichiometric ratio, so that the reactants can be effectively utilized. The preparation method of the present invention is simple, the production process is low in toxicity, the preparation parameters are easy to control, and it is easy to prepare for large-scale production, and has broad application prospects in the field of photocatalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite nanomaterials, and in particular to a lead-free, ligand-free halide perovskite nanomaterial and a preparation method and application thereof. Background Art

[0002] The efficient photoreduction of CO2 into value-added chemicals and usable fuels (such as CO, CH4, CH3OH, etc.) using solar energy under the action of photocatalysts has attracted worldwide attention for achieving sustainable development of mankind. At present, the development of efficient and low-cost photocatalyst materials is a research hotspot and core challenge in this field. In order to obtain the best photoreduction activity of CO2, a series of semiconductor photocatalysts for photocatalytic CO2 reduction have been screened and developed. Although a lot of work has been done on various photoreduction CO2 systems in terms of crystal plane adjustment, energy band adjustment, heterostructure construction, defect design, etc., no further breakthrough has been made in photocatalytic activity. In this context, metal halide perovskites (MHPs) have great potential in the field of photocatalytic CO2 reduction due to their remarkable optoelectronic properties such as excellent light absorption ability, long diffusion length of photogenerated carriers, and adjustable bandgap width.

[0003] However, in terms of MHPs photocatalysts, toxic lead-based MHPs have advantages over lead-free MHPs. The photoelectric performance of lead-free MHPs is worse than that of lead-based MHPs, and the photoreduction activity of CO2 is generally low, which is not conducive to the development of future industrialization. More importantly, these two perovskites cannot obtain excellent catalytic effects that match their inherent excellent photophysical properties due to poor electron transfer caused by the long-chain organic ligands at the end caps and less exposure of active sites.

[0004] Generally, rational nanostructure design is a necessary strategy to improve the intrinsic performance of photocatalysts. As a very attractive model, hollow nanostructures usually have many advantages over solid nanostructures, such as enhanced light absorption, reduced carrier and proton diffusion length, and larger specific surface area, which has been widely confirmed in previous studies. In short, the application of hollow structures in the field of perovskites can produce good results. However, due to its ionic nature, it is difficult to prepare special structures such as hollow nanostructures in MHPs, especially in the absence of surfactants. However, halide perovskites often show great catalytic potential in the absence of surfactants. Therefore, in order to improve the electronic transport performance between perovskites and other active materials and reactants, it is necessary to eliminate the interference caused by ligands. Post-synthetic ligand removal strategies usually lead to the aggregation of nanostructures, so it is necessary to exclude ligands during the synthesis process. However, due to the ionic nature, the synthesis environment restricts MHP NCs, and it is difficult to prepare special structures such as hollow nanostructures, not to mention the absence of surfactants. Summary of the invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the object of the present invention is to provide a lead-free ligand-free halide perovskite nanomaterial and a preparation method and application thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] The first aspect of the present invention provides a halide perovskite nanomaterial.

[0008] The second aspect of the present invention provides a method for preparing halide perovskite nanomaterials.

[0009] The third aspect of the present invention proposes an application of halide perovskite nanomaterials.

[0010] A fourth aspect of the present invention provides a method for simultaneously reducing carbon dioxide and oxidizing methanol.

[0011] According to a first aspect of the present invention, a halide perovskite nanomaterial is provided, wherein the halide perovskite is Cs3Sb2Br9, has a hollow spherical structure, an average particle size of 200 to 300 nm, and preferably an average particle size of 220 to 250 nm.

[0012] According to a second aspect of the present invention, there is provided a method for preparing the halide perovskite nanomaterial according to the first aspect, comprising the following steps:

[0013] S1: Dissolve SbBr3 in dimethyl sulfoxide (DMSO) and add CsBr to obtain a Cs3Sb2Br9 precursor solution;

[0014] S2: The Cs3Sb2Br9 precursor solution is quickly added to methyl acetate, stirred, centrifuged, the solid product is collected, washed, and dried to obtain the halide perovskite nanomaterial.

[0015] In the present invention, only DMSO is selected as the solvent in S1. If other organic solvents such as DMF are used, the reaction precursor of Cs3Sb2Br9 cannot be completely dissolved; in S2, only methyl acetate is selected as the anti-solvent, and other anti-solvents such as tert-butyl alcohol and isopropanol cannot obtain a hollow spherical structure. When the precursor solution contacts the anti-solvent, it needs to be injected quickly. This is due to the anti-solvent effect. The outer layer of the Cs3Sb2Br9 droplet rapidly nucleates and crystallizes to form an outer spherical shell. The formation of the outer spherical shell can slow down the mixing of DMSO in the droplet and the anti-solvent, which helps the formation of the hollow nanostructure. In the prior art, isopropanol is used as an anti-solvent. Since isopropanol has a relatively greater solubility in the constituent ions of perovskite and better miscibility with the aforementioned solvent DMSO, the droplet collapses into a solid solid before it has time to form an outer shell. The key to the growth mechanism of the present invention is to first form a layer of droplet shell, and then slowly penetrate through the solvent to gradually form a hollow spherical structure.

[0016] In some embodiments of the present invention, the molar ratio of SbBr3 to CsBr is 2.7-3.0:4.4-4.5.

[0017] In the present invention, other molar ratios of SbBr3 and CsBr cannot completely dissolve CsBr and SbBr3 to form a pure Cs3Sb2Br9 precursor solution.

[0018] In some embodiments of the present invention, the concentration of Cs3Sb2Br9 in the Cs3Sb2Br9 precursor solution is 0.13-0.15 mol / L.

[0019] In some embodiments of the present invention, the volume ratio of the Cs3Sb2Br9 precursor solution to ethyl acetate is 1:50-60.

[0020] In some preferred embodiments of the present invention, the stirring speed in S2 is 500-600 rpm and the stirring time is 8-12 min.

[0021] In some preferred embodiments of the present invention, the centrifugal speed in S2 is 5000-8000 rpm, and the time is 3-5 min.

[0022] In some preferred embodiments of the present invention, the washing in S2 is performed using an organic solvent, specifically: toluene is used first and then ethanol, and each solvent is centrifuged for at least three times, each time at 8000 rpm for 5 minutes.

[0023] In some preferred embodiments of the present invention, the drying in S2 is specifically: annealing at 130-150° C. for more than 6 hours, preferably 6-8 hours.

[0024] In the present invention, the above drying is to evaporate the DMSO organic solvent remaining in the nanomaterial to further achieve the hollowing effect.

[0025] According to a third aspect of the present invention, there is provided a use of the halide perovskite nanomaterial described in the first aspect in preparing a photocatalyst.

[0026] In some embodiments of the present invention, the photocatalyst is specifically a catalyst for catalyzing CO2 reduction.

[0027] In some embodiments of the present invention, the photocatalyst is specifically a catalyst for catalyzing methanol oxidation.

[0028] According to a fourth aspect of the present invention, a method for simultaneously reducing carbon dioxide and oxidizing methanol uses the halide perovskite nanomaterial described in the first aspect to simultaneously photocatalytically reduce carbon dioxide and oxidize methanol.

[0029] In some embodiments of the present invention, the product of the reduction of carbon dioxide includes carbon monoxide, and the product of the oxidation of methanol includes formic acid.

[0030] In some embodiments of the present invention, the simultaneous photocatalytic reduction of carbon dioxide and oxidation of methanol are performed under irradiation with simulated sunlight in the wavelength band above 400 nm.

[0031] The beneficial effects of the present invention are:

[0032] Without the need for surface ligands or complex etching technology, a new type of lead-free and ligand-free halide perovskite hollow nanospheres is prepared by a simple template-free method, which solves the problem of high toxicity of lead-based perovskites. The method of the present invention has low toxicity in the production process, simple operation, easy control of preparation parameters, and is easy to mass produce and prepare, and has broad application prospects in the field of photocatalysis.

[0033] The prepared hollow spherical nanostructured halide perovskite (H-Cs3Sb2Br9) as a photocatalyst has stronger light absorption ability, larger specific surface area, and better proton and carrier transfer compared with traditional solid nanostructured halide perovskite nanocrystals (N-Cs3Sb2Br9), which can effectively improve the performance of carbon dioxide reduction. In addition, since this photocatalyst has a ligand-free surface, it contains abundant Br vacancies, which can expose more reaction catalytic sites, thereby promoting the contact between the active sites and the reaction substrate, so as to achieve the purpose of improving the photocatalytic conversion activity of CO2 to CO. More importantly, the use of methanol oxidation at the oxidation end can produce formic acid close to the stoichiometric ratio, and obtain chemical products of higher value. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1TEM images of Cs3Sb2Br9 nanomaterials of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0035] Figure 2 1 and 2 are XRD diagrams of the Cs3Sb2Br9 nanomaterials of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.

[0036] Figure 3 Figure a is a comparison chart of the catalytic effects of the halide perovskite H-Cs3Sb2Br9 nanomaterial prepared in Example 1 of the present invention, the N-Cs3Sb2Br9NCs prepared in Comparative Example 1, and the B-Cs3Sb2Br9NCs prepared in Comparative Example 2 as photocatalysts for the reduction of carbon dioxide; and figure b is the ion chromatography curve of formic acid generated by the photocatalytic oxidation of methanol by the above three nanomaterials.

[0037] Figure 4 This is a diagram of the solid-gas photocatalytic reaction device in the experimental example. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0039] Example 1

[0040] This embodiment prepares a halide perovskite Cs3Sb2Br9 nanomaterial (H-Cs3Sb2Br9), and the specific process is as follows:

[0041] (1) 53.1 mg of SbBr3 was dissolved in 0.5 mL of DMSO, stirred for 20 min until completely dissolved, and then 46.9 mg of CsBr was added and stirred for 20 min until completely dissolved to obtain a Cs3Sb2Br9 precursor solution;

[0042] (2) 500 μL of Cs3Sb2Br9 precursor solution was quickly injected into 25 mL of methyl acetate, stirred at 500 rpm for 30 min, centrifuged at 5000 rpm for 3 min, the solid product was collected, and washed with toluene by centrifugation at 8000 rpm for 5 min, repeated three times, and then washed with ethanol three times, the solid precipitate was collected, and the collected solid was annealed in an oven at 150 ° C for 6 h to obtain a yellow-green powder, which is the halide perovskite H-Cs3Sb2Br9 nanomaterial.

[0043] Example 2

[0044] This embodiment prepares a halide perovskite Cs3Sb2Br9 nanomaterial (H-Cs3Sb2Br9), and the specific process is as follows:

[0045] (1) Dissolve 48.8 mg of SbBr3 in 0.5 mL of DMSO, stir for 20 min until completely dissolved, add 47.88 mg of CsBr, and stir for 20 min until completely dissolved to obtain a Cs3Sb2Br9 precursor solution;

[0046] (2) 500 μL of Cs3Sb2Br9 precursor solution was quickly injected into 25 mL of methyl acetate, stirred at 500 rpm for 30 min, centrifuged at 6000 rpm for 3 min, the solid product was collected, and washed with toluene by centrifugation at 7000 rpm for 5 min, repeated three times, and then washed with ethanol three times, the solid precipitate was collected, and the collected solid was annealed in an oven at 140 ° C for 7 h to obtain a yellow-green powder, which is the halide perovskite H-Cs3Sb2Br9 nanomaterial.

[0047] Example 3

[0048] This embodiment prepares a halide perovskite Cs3Sb2Br9 nanomaterial (H-Cs3Sb2Br9), and the specific process is as follows:

[0049] (1) 54.2 mg of SbBr3 was dissolved in 0.5 mL of DMSO, stirred for 20 min until completely dissolved, and then 47.30 mg of CsBr was added and stirred for 20 min until completely dissolved to obtain a Cs3Sb2Br9 precursor solution;

[0050] (2) 500 μL of Cs3Sb2Br9 precursor solution was quickly injected into 25 mL of methyl acetate, stirred at 500 rpm for 30 min, centrifuged at 8000 rpm for 3 min, the solid product was collected, and washed with toluene by centrifugation at 8000 rpm for 5 min, repeated three times, and then washed with ethanol three times, the solid precipitate was collected, and the collected solid was annealed in an oven at 140 ° C for 8 h to obtain a yellow-green powder, which is the halide perovskite H-Cs3Sb2Br9 nanomaterial.

[0051] Comparative Example 1

[0052] This comparative example prepares a ligand-containing, lead-free perovskite Cs3Sb2Br9 nanocrystal (N-Cs3Sb2Br9), and the specific process is as follows:

[0053] (1) First, prepare the precursor of Cs-oleic acid: 162.9 mg of Cs2CO3, 4.0 mL of 1-octadecene and 0.5 mL of oleic acid were mixed in a three-necked flask and vacuum degassed at 120°C for 1 h; then, the temperature was raised to 150°C under argon and stirred vigorously for 3 h until the solution became clear to obtain solution A, which was then cooled to room temperature for the next step;

[0054] (2) Preparation of Cs3Sb2Br9 nanocrystals: 36.1 mg of SbBr3, 10.0 mL of 1-octadecene, 0.4 mL of oleylamine and 1.0 mL of octanoic acid were mixed in a three-necked flask and degassed under vacuum at 80 °C for 1 h. The mixture was heated to 180 °C under argon to obtain solution B.

[0055] (3) 0.3 mL of the cooled solution A was quickly injected into the solution B. After 60 seconds, the solution was cooled with liquid nitrogen and centrifuged at 7800 rpm for 3 minutes. The precipitate C was extracted and washed with n-hexane for 3 times. The precipitate C was dried at 60 °C for 6 hours to obtain Cs3Sb2Br9 nanocrystalline powder.

[0056] Comparative Example 2

[0057] This comparative example prepares a ligand-containing, lead-free perovskite Cs3Sb2Br9 nanoblock (B-Cs3Sb2Br9). The difference from comparative example 1 is that comparative example 1 uses a traditional hot injection method, while this comparative example uses an anti-solvent method. The specific process is as follows:

[0058] (1) Dissolve 173.5 mg of SbBr3 in 4 mL of DMSO, stir for 30 min until completely dissolved, add 127.7 mg of CsBr, and stir for 10 min to obtain precursor solution A;

[0059] (2) Add 4 mL of oleic acid to 36 mL of chloroform and stir for 10 min to prepare the antisolvent;

[0060] (3) The precursor solution A was quickly added to 40 mL of the above anti-solvent and centrifuged at 8000 rpm for 5 minutes. The solid product was washed with toluene three times and dried at 60 °C for 12 h to obtain yellow-green B-Cs3Sb2Br9.

[0061] Test example

[0062] The products prepared in the examples and comparative examples were subjected to structural characterization and application effect tests. TEM images of Cs3Sb2Br9 of Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 1As shown, a is the H-Cs3Sb2Br9 prepared in Example 1, and it can be seen that its morphology is hollow nanospheres, and the average particle size of the hollow nanospheres is 220-300nm. The products prepared in the other examples are similar to Example 1 and are not repeated here; b is the N-Cs3Sb2Br9 prepared in Comparative Example 1, and it can be seen that its morphology is nanocrystals, and the average particle size of the nanocrystals is about 30nm; c is the B-Cs3Sb2Br9 prepared in Comparative Example 2, and it can be seen that its morphology is irregular nanoblocks, and the average diameter of the nanoblocks is about 500nm.

[0063] The XRD patterns of Cs3Sb2Br9 of Example 1, Comparative Example 1 and Comparative Example 2 are as follows: Figure 2 shown.

[0064] The test conditions are: copper target Kα ray, 2θ scanning range of 10-60°, scanning speed of 15° / min, voltage of 40kV. The prepared H-Cs3Sb2Br9, N-Cs3Sb2Br9 and B-Cs3Sb2Br9 can be indexed as P-3m1(164) hexagonal space group (PDF card number 04-009-0964), with high crystallinity characteristics of strong diffraction peaks at 22.4°, 27.5°, 31.9°, 39.3° and 45.7°, which match well with (012), (201), (022), (212) and (204) planes, respectively.

[0065] The catalytic effects of Cs3Sb2Br9 in Example 1, Comparative Example 1 and Comparative Example 2 for photocatalytic reduction of carbon dioxide and oxidation of methanol were tested respectively: Figure 4 As shown, xenon (Xe) was used to simulate sunlight irradiation, and a 400nm filter was set. The Cs3Sb2Br9 of Example 1, Comparative Example 1, and Comparative Example 2 were carried out in a closed solid-gas photocatalytic reaction device filled with CO2, H2O, and methanol. After a certain period of illumination, the product was obtained for the next test: the obtained gas phase product was tested by gas chromatography, and the liquid phase product was tested by ion chromatography. The results are as follows Figure 3 shown.

[0066] Cs3Sb2Br9 perovskite can effectively convert CO2 into CO. The CO production curves of H-Cs3Sb2Br9, N-Cs3Sb2Br9 and B-Cs3Sb2Br9 over time show obvious differences in photocatalytic activity. Compared with N-Cs3Sb2Br9 and B-Cs3Sb2Br9, H-Cs3Sb2Br9 prepared in Example 1 exhibits significant photocatalytic CO2 reduction activity, as shown in Figure 2. Figure 3 The CO production test results in Figure a. The CO production of H-Cs3Sb2Br9 reached 5059.6 μmol g -1After 8 h of photocatalytic reaction, it was almost 13 times that of N-Cs3Sb2Br9 (400.0 μmol g -1 ), which is much higher than the photocatalytic effect of B-Cs3Sb2Br9 (94.3 μmol g -1 ). This improvement in photocatalytic activity is mainly attributed to the hollow nanosphere structure of H-Cs3Sb2Br9 exposing abundant catalytic sites and enhancing light collection capacity. While reducing carbon dioxide, formic acid is also obtained in a nearly stoichiometric ratio. The results of the formic acid test are shown in Figure 3 The effects of the remaining embodiments are similar to those of embodiment 1, and will not be described in detail.

[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a halide perovskite nanomaterial, characterized in that: The steps include: S1: Dissolve SbBr3 in dimethyl sulfoxide and add CsBr to obtain a Cs3Sb2Br9 precursor solution; S2: quickly adding the Cs3Sb2Br9 precursor solution into methyl acetate, stirring, centrifuging, collecting the solid product, washing, and drying to obtain the halide perovskite nanomaterial; Wherein, the halide perovskite is Cs3Sb2Br9, and the halide perovskite nanomaterial has a hollow spherical structure with an average particle size of 200-300 nm.

2. The method for preparing the halide perovskite nanomaterial according to claim 1, characterized in that: The molar ratio of SbBr3 to CsBr is 2.7~3.0:4.4~4.

5.

3. The method for preparing the halide perovskite nanomaterial according to claim 1, characterized in that: The drying described in S2 specifically includes: annealing at 130-150°C for more than 6 hours.

4. The method for preparing the halide perovskite nanomaterial according to claim 1, characterized in that: The washing in S2 is performed using an organic solvent, specifically: washing with toluene first and then with ethanol, and washing with each solvent at least three times.

5. The method for preparing halide perovskite nanomaterial according to claim 1, characterized in that: The centrifugation speed in S2 is 5000-8000 rpm, and the time is 3-5 min.

6. A halide perovskite nanomaterial, characterized in that: The method comprises adopting the preparation method described in any one of claims 1 to 5.

7. Use of the halide perovskite nanomaterial according to claim 6 in the preparation of photocatalysts.

8. A method for simultaneously reducing carbon dioxide and oxidizing methanol, characterized in that: The halide perovskite nanomaterial according to claim 6 is used to simultaneously photocatalytically reduce carbon dioxide and oxidize methanol.

9. The method for simultaneously reducing carbon dioxide and oxidizing methanol according to claim 8, characterized in that: The product of the reduction of carbon dioxide includes carbon monoxide, and the product of the oxidation of methanol includes formic acid.

10. The method for simultaneously reducing carbon dioxide and oxidizing methanol according to claim 8, characterized in that: The simultaneous photocatalytic reduction of carbon dioxide and oxidation of methanol are carried out under irradiation of simulated sunlight with a wavelength of 400 nm or more.

Citation Information

Patent Citations

  • Preparation method for perovskite type composite oxide hollow nanomaterial

    CN102320656A

  • Perovskite hollow ball catalyst having high activity, and preparation and application

    CN103357396A